MACROSCOPIC OBSERVATION OF Bacillus sp. AT THE UPT PROTECTION OF FOOD CROPS AND HORTICULTURE IN EAST JAVA - Ayu Sintiyah; Inayah Fitri; Slamet Ifandi (Jurnal Matematika dan Sains (JMS), 2022)
Bacillus sp. are gram positive bacteria. Thesa bacteria are able to decompose complax compounds into simpler compounds, to reduce thze negative effects of chemical pesticides, it is necessary to develop alternative methods that are safer and environmentally friendly to control plant diseases. This macroscopic observation only looks at the colony and cannot tell whether these bacteria have an effect on plants. Bacillus sp. it includes a distinct physiological group of on-pathogenic bacteria, which are realitively easy to manipulate genetically and simple to cultuure, which strengthens their suitability for industrial purposes. Macroscopic observation of Bacillus sp. this gets the number of colonies ±20. Further observation are needed to find aot whether it is good for use for the community.